Nilai-Nilai Penguatan Pendidikan Karakter Berbasis Neurosains dalam Pembelajaran Akidah Akhlak di SD Negeri Serayu - Us'an, Us'an; Putra, Armando Bima (Institut Agama Islam Negeri Curup, 2024)
This research examines the values of strengthening neuroscience-based character education in learning moral beliefs at Serayu State Elementary School. Moral beliefs are a subject that emphasizes the ability to understand faith, manners, and the good relationship between humans and God. However, learning moral beliefs tends to touch the cognitive domain which is limited to material mastery, while the affective domain is forgotten. Therefore, the aim of this research is to find a new concept in instilling character values in the learning of moral beliefs. This research uses a qualitative approach with descriptive methods. Data collection techniques include interviews, observation and documentation. Researchers use data analysis by collecting data, reducing data, presenting data, and drawing conclusions. The data that has been collected is then described and given meaning, from that meaning a conclusion is drawn. The results of this research show the values of strengthening neuroscience-based character education in learning moral beliefs, namely: regulatory religious values from the temporal lobe of the brain, regulatory mutual cooperation values from the cingulate gyrus and basal ganglia, regulatory nationalist attitudes from the prefrontal cortex, regulatory integrity attitudes from the system. limbic, and self-regulatory attitudes of the cerebellum. If neuroscience-based character education in moral belief lessons is carried out optimally, then this character education can be achieved optimally. The reason is that changing students' behavior is more effective by changing their brains first.